On the problem of vocational guidance organization children with sight violations - CHERKASOVA, Irina (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2014)
The author considers the organization of vocational guidance of childrenwith sight violations. Some psychological problems of these children are openedin article.